Microstructure and thermoelectric characteristics of (ZnO)k×In2O3: Based ceramics (k = 5 and 11) - Slavko Bernik; Mateja Košir; Emmanuel Guilmeau (Zaštita Materijala)
Oxide thermoelectric ceramics are needed for high-temperature applications that involve harvesting the waste heat by direct transformation into electricity. In the case of n-type materials, the homologous (ZnO)kIn2O3-type phases are very promising for tailoring the TE properties. In this investigation the thermoelectric (ZnO)kIn2O3-based ceramics for k=5 and 11 were prepared using a classic ceramics procedure and sintering at 1500oC. During their preparation, either a fresh powder mixture of ZnO and In2O3 or a mixture of ZnO and In2O3 also containing plate-like grains of the pre-reacted (ZnO)kIn2O3 phases was used to induce possible microstructure texturing. It was demonstrated that the starting composition in terms of k value and the type of starting powder mixture affect the processes, leading to the formation of the equilibrium (ZnO)kIn2O3 homologous phase and, consequently, also the microstructure development. Nevertheless, all the samples had similar final microstructures and no texturing was observed. Regardless of the use of different starting-powder mixtures, the samples with the same composition had a similar ZT: at 627oC it was 0.11 for the samples with k=5 and 0.08 for k=11, which is not so inferior if we take account of the significantly lower content of In2O3 in these samples.